Dental age and tooth development in children with molar-incisor hypomineralization: A case-control study - (:unkn) unknown (Elsevier Ltd, 2022)
Objective: The aim of the study was to determine the dental age for the evaluation of tooth development in children with molar-incisor hypomineralization (MIH) by using the Willems method, Cameriere-European formula, and London Atlas. Design: Panoramic radiographs of 308 children between the ages of 6–13 diagnosed with MIH and the same number of sex- and age-matched children without MIH were evaluated by two different examiners using the Willems method, Cameriere-European formula, and London Atlas. The mean difference between chronological age and dental age in both groups was calculated for each sex and age. The mean absolute error was used to determine the accuracies of the Willems method, Cameriere-European formula, and London Atlas. Results: There was a statistically significant difference found only in Willems method in dental age estimation between the groups with and without MIH (P = 0.001). In the evaluation performed with Cameriere-European formula and London Atlas, which are more accurate methods for dental age estimation in both groups, no statistically significant difference was found in dental age estimation between the two groups (P = 0.322, P = 0.290, respectively). There was a statistically significant intense linear correlation for three methods in both groups (P < 0.001). Conclusions: MIH, which is a developmental enamel defect, does not affect dental age and tooth development since there was no significant difference between groups with and without MIH according to the evaluations made with accurate dental age estimation methods. © 2021 Elsevier Ltd
Keywords: Dental age estimation; Dental development; Molar-incisor hypomineralization